Electrical Properties of Al-Doped CdO Thin Films Prepared by Thermal Evaporation in Vacuum - Ngamnit Wongcharoen; Thitinai Gaewdang; Tiparatana Wongcharoen (My University, 2012)
In this work, thin films of undoped and Al-doped CdO with 3, 5, 7 and 9 wt.% were prepared by thermal evaporation in vacuum on glass substrate. From XRD patterns, doping CdO films with Al up to 7% causes small reduction in the intensity of the (200) plane, while small increase is observed in the intensity of (111) plane. However, intensity of all peaks rapidly decreases for the films with high Al content (9%). The formation of tubular nanostructures of undoped and Al doped-CdO films was observed by SEM technique. Energy gap value of the films was evaluated from the optical transmission spectra in the spectral region 300-1000 nm. The best values of electrical conductivity, Hall mobility and electron concentration were obtained in the films with 5% Al doping. Temperature dependent resistivity measurements of the films doped with Al at 3, 5 and 7% showed the metal-semiconductor transition around 100, 150 and 205 K respectively, which is rationalised by localisation of degenerate electrons in a weak-localisation regime. It was also found that the transition temperature is dependent on the Al concentration and is related to the increase in disorder induced by dopant addition.
Keywords: Vacuum evaporation; Degenerate semiconductor; ZnO doping and properties